Prophets as performers: biblical performance criticism and Israel's prophets - Mathews, Jeanette (Cascade Books, 2020)
The biblical prophets and Biblical Performance Criticism are brought together in three case studies (Elijah, Ezekiel, Jonah) presented as performances. This book proposes a new method of reading the biblical prophets with a threefold focus on creativity, commentary, and connections. With this method the many and varied performances of the prophets can be better appreciated. Critical analysis of the quintessentially performative nature of the prophets as embodied spokespersons for YHWH aids us in understanding and clarifying YHWH's message to audiences, situations, and communities of the past as well as engaging contemporary audiences. --Back Cover